Age related decrease of NOR activity in bone marrow metaphase chromosomes from healthy individuals - Pedrazzini, Estela Maris (1998)
Aims—To present data obtained from human bone marrow preparations from healthy individuals showing that the proportion of metaphases with silver stained nucleolar organiser region (AgNOR) chromosomes is associated with the age of the donor. Methods—Bone marrow preparations from eight Russian and 10 Argentinian healthy individuals donating bone marrow for heterologous transplantation were studied by silver staining. The Russian bone marrow preparations were used directly, while the bone marrow specimens from Argentinian donors were incubated for 24 hours at 37°C in F-10 medium with 15% fetal bovine serum. The slides were silver stained by the one step method of Howell and Black with slight modifications. Thirty metaphases with clearly defined D and G group chromosomes were scored for the numbers of AgNORs. All metaphases that were adjacent to silver stained interphase nuclei were analysed to assess the percentage of AgNOR positive mitoses. The Kruskal Wallis test and Kendall’s rank correlation coeYcient (rK) were used to assess the relation between age and the percentage of AgNOR positive cells. Results—The mean numbers (SE) of AgNORs per metaphase were 5.06 (0.17) and 5.56 (0.23) for the Russian and Argentinian groups, respectively, with no significant diVerences between the two groups. The common percentage of AgNOR positive cells decreased significantly as a function of age, with an rK = −0.57 (p < 0.0012). Conclusions—The percentages of AgNOR negative metaphases in bone marrow from healthy individuals is strongly associated with age and this may be related to age related telomere loss.